Segregation in the Twenty First Century: Processes, Complexities and Future Directions. (20th February 2019) - Piekut, Aneta; Pryce, Gwilym; van Gent, Wouter
Abstract: Economic inequality, international migration and urban transformation have generated fresh interest in segregation and given new social significance to questions of socio‐spatial separation and interaction. At the same time, advances in data, methods and theory are opening up new avenues of inquiry that push the focus beyond simple measures of unevenness of residential patterns towards more nuanced analysis of spatial asymmetry, structure and scale. There is also a drive towards considering spaces and activities outside the neighbourhood, bringing new richness to our understanding of how various social groups interact in the various aspects of their lives. These processes and complexities form the backdrop for our special issue and we reflect on the implications for future priorities in research on segregation in the twenty first century.